2018
DOI: 10.1111/jbi.13241
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics and historical biogeography of the genusGerrhonotus(Squamata: Anguidae)

Abstract: Aim: Multiple geological and climatic events have created geographical or ecological barriers associated with speciation events, playing a role in biological diversification in Mexico. Here, we evaluate the influence of Neogene geological events and of Pleistocene climate change in the diversification of the genus Gerrhonotus using molecular dating and ancestral area reconstruction. Location: Mexico and south-central United States.Methods: A multilocus sequence dataset was generated for 86 individuals of Gerrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 54 publications
12
28
1
Order By: Relevance
“…In our study, we treated G. lugoi and G. parvus as separate taxa within the genus Gerrhonotus pending further investigation. A paraphyletic Gerrhonotus infernalis also was previously inferred ( García-Vázquez et al, 2018a ). All specimens of G. infernalis included in our study are from Texas.…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations
“…In our study, we treated G. lugoi and G. parvus as separate taxa within the genus Gerrhonotus pending further investigation. A paraphyletic Gerrhonotus infernalis also was previously inferred ( García-Vázquez et al, 2018a ). All specimens of G. infernalis included in our study are from Texas.…”
Section: Methodsmentioning
confidence: 78%
“…Phylogenetic analysis of molecular data suggested that G. parvus is most closely related to species in Gerrhonotus ( Conroy et al, 2005 ; Leavitt et al, 2017 ). The monophyly of Gerrhonotus and the inclusion of both G. parvus and G. lugoi within Gerrhonotus was questioned in a more recent analysis ( García-Vázquez et al, 2018a ). Those authors found that the phylogenetic position of G. parvus as sister to all Gerrhonotus , excluding G. lugoi , was not strongly supported in all analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these analyzed the uplift of the Colorado Plateau‐Sierra Madre Occidental mountain range dividing the Sonoran and Chihuahuan deserts (Gámez et al, ; Jaeger et al, ; Leaché & Mulcahy, ; Rebernig et al, ; Riddle, ; Riddle & Hafner, ) , and focused either on widely distributed species (e.g., Rebernig et al, ) or several species (e.g., Leaché & Mulcahy, ; Riddle & Hafner, ). However, other physiographic and hydrographic events occurred in the CD during the Neogene and may have favored the diversification of the biota but little is known about these events (e.g., Bryson, Jaeger, Lemos‐Espinal, & Lazcano, ; García‐Vázquez, Nieto‐Montes de Oca, Bryson, Schmidt‐Ballardo, & Pavón‐Vázquez, ; Myers et al, ). The late Neogene (i.e., Pliocene) in the CD was marked by the formation of lakes established at the bottoms of the major bolsons (Axtell, ; Morafka, ).…”
Section: Introductionmentioning
confidence: 99%